(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Abstract: Nutraceuticals and functional foods have emerged as promising agents in the prevention and treatment of various diseases, driven by their bioactive components that offer health benefits beyond basic nutrition. This paper explores the synergistic potential of nutraceuticals and functional foods in combating chronic diseases such as cardiovascular disorders, diabetes, obesity, and cancer. By integrating traditional dietary approaches with modern nutritional science, these functional foods and nutraceuticals present an innovative pathway to enhance health outcomes and reduce the burden of disease. The paper delves into the mechanisms by which specific nutraceuticals, including polyphenols, omega-3 fatty acids, probiotics, and dietary fibers, exert their protective effects. It also discusses the role of functional foods, such as fortified cereals, fermented products, and bioactive-rich fruits and vegetables, in modulating metabolic pathways and supporting immune function. Emphasis is placed on the synergistic effects of combining these bioactive compounds, which can lead to enhanced efficacy in disease prevention and management. Through a comprehensive review of recent clinical studies and meta-analyses, this paper highlights the therapeutic potential of incorporating nutraceuticals and functional foods into daily diets. Additionally, the paper addresses challenges such as bioavailability, regulatory frameworks, and consumer acceptance, which must be overcome to fully harness the benefits of these interventions. In the synergistic approach of combining nutraceuticals and functional foods offers a promising avenue for disease prevention and treatment, emphasizing the need for continued research and collaboration between healthcare professionals, nutritionists, and the food industry.